2011
DOI: 10.1143/apex.4.115601
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Distribution of NN and NNO Complexes in Cast-Grown Multicrystalline Silicon for Photovoltaic Cells

Abstract: Multicrystalline silicon grown by the cast method and used in photovoltaic cells includes nitrogen from the Si3N4 coating of the SiO2 crucible. We investigated the distribution of nitrogen, existing as NN or NNO complexes in silicon, by Fourier transform infrared spectroscopy. We found that the NN peak intensity was higher at the upper part of the silicon ingot, while the NNO peak intensity was higher at the lower part. There was a complementary relationship between the distribution of NN and that of NNO; this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Control of these light-element impurities, i.e., interstitial oxygen (O i ) and substitutional carbon (C s ), has become essential because light-element impurities affect solar sell performance through defect formation. [17][18][19][20][21][22][23][24][25][26][27] It is necessary to accurately clarify the mechanism of generation of the light-element impurities in Si crystals grown by the seed-casting method to develop methods to suppress the degradation in solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Control of these light-element impurities, i.e., interstitial oxygen (O i ) and substitutional carbon (C s ), has become essential because light-element impurities affect solar sell performance through defect formation. [17][18][19][20][21][22][23][24][25][26][27] It is necessary to accurately clarify the mechanism of generation of the light-element impurities in Si crystals grown by the seed-casting method to develop methods to suppress the degradation in solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen occupies an interstitial site (Oi) and carbon a substitutional site (Cs), and nitrogen exists as complexes called NN and NNO in the silicon crystal. 4) These impurities are often inhomogeneously distributed as a result of segregation in the crystal, 5) and if the concentration of these light-element impurities was above the solid-solubility limit, precipitation would occur. [6][7][8] These precipitates may degrade the conversion efficiency of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration ratio NN/NNO might depend on the O concentration and also on the crystal defects that are inhomogeneously distributed inside of the Si ingot. Kusunoki et al 6) reported that NN and NNO are complementally distributed in the cast-grown multicrystalline silicon ingot. This inhomogeneous distribution of the NN/NNO ratio is probably caused by inhomogeneously distributed crystal defects.…”
mentioning
confidence: 99%